2021
DOI: 10.31234/osf.io/4vyjs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relative salience of numerical and non-numerical dimensions shifts over development: A re-analysis of Tomlinson, DeWind, and Brannon (2020)

Abstract: Visual displays of objects include information about number and other magnitudes such as cumulative surface area. Despite the confluence of cues, a prevalent view is that number is uniquely salient within multidimensional stimuli. Consistent with this view, Tomlinson, DeWind, and Brannon (2020) report that, in addition to greater acuity for number than area among both children and adults, number biases area judgments more than the reverse, at least in childhood. However, a failure to consider perceived area, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Recent evidence from our lab, however, goes against the uniqueness claim. For example, we found that when perceptual discriminability between number and cumulative area was matched, area biased children's number judgments more than the reverse (Aulet & Lourenco, 2021b) and children sorted visual stimuli according to area, not number (Aulet & Lourenco, 2021c), suggesting greater intrinsic salience for nonnumerical magnitude, and consistent with others who have argued against the uniqueness of number Newcombe, Levine, & Mixs, 2015). Similarly, Testolin, Dolfi, Rochus, and Zorzi (2020) found that the internal encoding of "mature" computational networks, trained to discriminate stimuli according to number, treated total perimeter and convex hull as comparable to number.…”
Section: Introductionsupporting
confidence: 88%
“…Recent evidence from our lab, however, goes against the uniqueness claim. For example, we found that when perceptual discriminability between number and cumulative area was matched, area biased children's number judgments more than the reverse (Aulet & Lourenco, 2021b) and children sorted visual stimuli according to area, not number (Aulet & Lourenco, 2021c), suggesting greater intrinsic salience for nonnumerical magnitude, and consistent with others who have argued against the uniqueness of number Newcombe, Levine, & Mixs, 2015). Similarly, Testolin, Dolfi, Rochus, and Zorzi (2020) found that the internal encoding of "mature" computational networks, trained to discriminate stimuli according to number, treated total perimeter and convex hull as comparable to number.…”
Section: Introductionsupporting
confidence: 88%
“…However, even in the face of statistical learning, non-numerical magnitudes remain more salient, and thus, must be inhibited in order to successfully attend to, and discriminate, number. Although there is accumulating evidence that area may be more salient than number early in development (Aulet & Lourenco, 2021a, 2021cHenik, Gliksman, Kallai, & Leibovich, 2017)…”
Section: The Magnitude Sense Accountmentioning
confidence: 99%
“…Yet a reanalysis of those data accounting for additive area suggested this may not be the case. Indeed, when accounting for additive area, the opposite may be true: area biases number judgments (Aulet & Lourenco, 2021).…”
Section: Area Perception In Childrenmentioning
confidence: 99%